Antibodies against invasive phenotype-specific antigens increase Mycobacterium avium subspecies paratuberculosis translocation across a polarized epithelial cell model and enhance killing by bovine macrophages - Everman, Jamie; Bermudez, Luiz (Frontiers in Cellular and Infection Microbiology, 2015)
Johne’s disease, caused by Mycobacterium avium subspecies paratuberculosis (MAP), is a severe chronic enteritis which affects large populations of ruminants globally. Prevention strategies to combat the spread of Johne’s disease among cattle herds involve adhering to strict calving practices to ensure young susceptible animals do not come in contact with MAP-contaminated colostrum, milk, or fecal material. Unfortunately, the current vaccination options available are associated with high cost and suboptimal efficacy. To more successfully combat the spread of Johne’s disease to young calves, an efficient method of protection is needed. In this study, we examined passive immunization as a mode of introducing protective antibodies against MAP to prevent the passage of the bacterium to young animals via colostrum and milk. Utilizing the infectious MAP phenotype developed after bacterial exposure to milk, we demonstrate that in vitro opsonization with serum from Johne’s-positive cattle results in enhanced translocation across a bovine MDBK polarized epithelial cell monolayer. Furthermore, immune serum opsonization of MAP results in a rapid host cell-mediated killing by bovine macrophages in an oxidative-, nitrosative-, and extracellular DNA trap-independent manner. This study illustrates that antibody opsonization of MAP expressing an infectious phenotype leads to the killing of the bacterium during the initial stage of macrophage infection.